Pengujian Dan Penerapan Manajemen Kas RW Dengan Metode Black Box - Hardianto, H; Hardianti, Fazrin Putri; Irawan, Reza Riyaldi; Harits, Dalhats Abiyyu Idzal; Turmudi, Ahmad (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Software testing is an important part of application development to ensure its quality and reliability. The study uses the Black Box method to perform partitioning equivalence testing on RW cash management applications. The aim of this study is to find errors and bugs in the application so that they can be fixed before used by the user. Test results show that applications that meet the specifications in the expected output table do not experience error gaps.